PANDANGAN ALKITAB TENTANG OKULTISME - Minggus Dilla (Sekolah Tinggi Teologi Arastamar Bengkulu, 2015)
Occult practices have occurred since time immemorial, and even today occult practices cannot be separated from the lives of believers and humans in general. What are occult practices and how can occult practices occur and what are the impacts on human life. In this paper, the author will explain the biblical view of the occult and its ins and outs so that believers can know and be able to avoid various kinds of occult practices that are around us.